PENGARUH PERILAKU KEPEMIMPINAN, MOTIVASI, DAN DISIPLIN KERJA TERHADAP EFEKTIVITAS KERJA PADA PUSKESMAS BUARAN KECAMATAN BANTARKAWUNG KABUPATEN BREBES - Kharis Maulana; Fatwa Zuhaena; Andi Johan (Majalah Imiah Manajemen & Bisnis, 2019)
This research is entitled: "The Influence of Leadership Behavior, Motivation, and Work Discipline on Work Effectiveness in Puskesmas Buaran Sub-district Bantarkawung Brebes Regency". The purpose of this study was to determine the significant effect of leadership behavior on Work Effectiveness at the Puskesmas Buaran Sub-district Bantarkawung Brebes Regency, to determine the effect of motivation on Work Effectiveness at the Puskesmas Buaran Kecamatan Bantarkawung Brebes Regency, and to determine the significant effect of work discipline on Effectiveness Work at the Puskesmas Buaran Sub-district Bantarkawung Brebes Regency. The hypothesis of this study are: 1). Leadership behavior has a significant influence on the effectiveness of the Work at the Puskesmas Buaran Sub-district Bantarkawung Brebes Regency, 2). Motivation has a significant effect on the effectiveness of the Work at the Puskesmas Buaran Sub-district Bantarkawung Brebes Regency, 3). Work Discipline has a significant influence on the effectiveness of the Work at the Puskesmas Buaran Sub-district Bantarkawung Brebes Regency. To test the effect of independent variables on the dependent variable, multiple linear regression analysis is used and based on the analysis results obtained tX1 value of 2.014, tX2 of 0.529, tX3 of 5.190, t count of tX1 and tX2 greater than t table (2.009), which means behavior leadership and work discipline affect work effectiveness, while motivation does not affect work effectiveness